OLFM2 promotes epithelial-mesenchymal transition, migration, and invasion in colorectal cancer through the TGF-β/Smad signaling pathway - Yong Tang; Yi Liu; Xiaobo Wang; Haiyang Guo; Lin Chen; Guangbing Hu; Yutong Cui; Shiqi Liang; Ji Zuo; Zichen Luo; Xinrui Chen; Xianfei Wang (BMC Cancer, 2024)
Abstract Background Colorectal cancer (CRC) is an aggressive tumor of the gastrointestinal tract, which is a major public health concern worldwide. Despite numerous studies, the precise mechanism of metastasis behind its progression remains elusive. As a member of the containing olfactomedin domains protein family, olfactomedin 2 (OLFM2) may play a role in tumor metastasis. It is highly expressed in colorectal cancer, and its role in the metastasis of CRC is still unclear. As such, this study seeks to explore the function of OLFM2 on CRC metastasis and its potential mechanisms. Methods Real-time fluorescence quantitative PCR and western blotting were used to study the expression of OLFM2 in human CRC and adjacent normal tissues. Knockdown and overexpression OLFM2 cell lines were constructed using siRNA and overexpression plasmids to explore the role of OLFM2 in the migration and invasion of CRC through transwell, and wound healing experiments. Finally, the expression of epithelial-mesenchymal transition (EMT) -related proteins and TGF-β/Smad signaling pathway-related proteins was investigated using western blotting. Results In this study, we observed an elevation of OLFM2 expression levels in CRC tissues. To investigate the function of OLFM2, we overexpressed and knocked down OLFM2. We discovered that OLFM2 knockdown inhibited migration and invasion of colon cancer cells. Furthermore, E-cadherin expression increased while N-cadherin and Vimentin expression were opposite. It is no surprise that overexpressing OLFM2 had the opposite effects. We also identified that OLFM2 knockdown resulted in reduced TGF-βR1 and downstream molecules p-Smad2 and p-Smad3, which are related to the TGF-β / Smad pathway. In contrast, overexpressing OLFM2 significantly boosted their expression levels. Conclusion The protein OLFM2 has been identified as a crucial determinant in the progression of CRC. Its mechanism of action involves the facilitation of EMT through the TGF-β/Smad signaling pathway. Given its pivotal role in CRC, OLFM2 has emerged as a promising diagnostic and therapeutic target for the disease. These results indicate the potential of OLFM2 as a valuable biomarker for CRC diagnosis and treatment and highlight the need for further research exploring its clinical significance.